In the Name of “Freedom” and “Democracy”: Causes of Voting for the Radical Right in the Czech Republic - Maškarinec, Pavel; Novotný, Lukáš (Communist and post-communist studies, 2024)
This article examines the rise of the populist radical right in the Czech Republic, where this party family had no parliamentary representation for many years. We show that by clarifying its ideological profile, the SPD achieved results in accordance with the social marginality and welfare chauvinism hypothesis. This is also confirmed by a spatial analysis, which shows that success of the SPD relied especially on mobilizing voters in traditional strongholds of the Czech left. In contrast, the Czech case yielded only very small support for the group threat effect and only mixed results for a U-shaped effect of age.